ANALISIS KEMAMPUAN MAHASISWA IAIN PALU MENYUSUNKALIMAT EFEKTIF DALAM SKRIPSI - Rustam Rustam (ISTIQRA, 2016)
The development of a scientific essay writing skills among students have been carried from the mastery of language elements to the ability to carry out the stages of creative writing process. The development of writing skills among religious colleges in particular; STAIN), IAIN), and UIN is not specifically taught. Implementation is only through learning Indonesian courses and writing scientific papers as general basic subjects (MKDU) and university compulsory subjects (MKWU) and depending on the syllabus and curriculum taught by a lecturer of Indonesian subjects. While the development of the teaching of scientific essay writing skills at public colleges are taught exclusively at universities with faculties and majors and programs of study Indonesian language and literature through the course of writing and summary writing scientific papers.The ability of the students IAIN Palu deemed not meet the criteria of the framework of writing scientific papers but requires analysis of truth in terms of the rules of the language is good and right in accordance with the enhanced spelling